All’s well that ends (and peaks) well? A meta-analysis of the peak-end rule and duration neglect - Alaybek, Balca; Dalal, Reeshad S.; Fyffe, Shea; Aitken, John A.; Zhou, You; Qu, Xiao; Roman, Alexis; Baines, Julia I. (Organizational behavior and human decision processes, 2022)
•The peak-end rule is an efficient heuristic for evaluating past experiences.•The meta-analytic peak-end effect is large and robust across moderators examined.•The peak-end effect is stronger than the duration, beginning, and trough effects.•The peak-end effect is stronger than the trend and variability effects.•The peak-end effect is comparable to the overall average effect. The peak-end rule (Fredrickson & Kahneman, 1993) asserts that, when people retrospectively evaluate an experience (e.g., the previous workday), they rely more heavily on the episode with peak intensity and on the final (end) episode than on other episodes in the experience. We meta-analyzed 174 effect sizes and found strong support for the peak-end rule. The peak-end effect on retrospective summary evaluations was: (1) large (r = 0.581, 95% Confidence Interval = 0.487–0.661), (2) robust across boundary conditions, (3) comparable to the effect of the overall average (mean) score and stronger than the effects of the trend and variability across all episodes in the experience, (4) stronger than the effects of the first (beginning) and lowest intensity (trough) episodes, and (5) stronger than the effect of the duration of the experience (which was essentially nil, thereby supporting the idea of duration neglect; Fredrickson & Kahneman, 1993). We provide a future research agenda and practical implications.